Non-Supersymmetric AdS Solutions in Type IIB String Theory - Wikström, Johan (My University, 2023)
The task of finding a satisfactory theory of quantum gravity has turned out to be extremely challenging. In the context of string theory, which is a potential frame work of quantum gravity, this problem is represented by the vast number of possible string compactifications. The swampland program is an effort to sort through these possibilities and define what makes some theories of quantum gravity inconsistent. The result is a number of so-called swampland conjectures. This thesis studies an AdS vacuum in type IIB string theory that is relevant to one of these conjectures. It is explicitly shown that this vacuum, which is an S-fold of the form AdS4 × S 1 × S 5 , satisfies the type IIB equations of motion. The S-fold originates from uplifting a non-compact gauging of the 4-dimensional N = 8 supergravity. A more simple case illustrating non-compact gaugings, related to the gauge group SO(8), is treated here. Also discussed is the topology of the S-fold, which features a non-trivial SL(2, Z) monodromy when the S 1 is encircled, making the background non-geometric. The connection to the swampland program appears when a 2-parameter deformation of the AdS vacuum is used to break supersymmetry. Locally, these deformations only amount to a coordinate redefinition, which protects the vacuum solution from some non-perturbative decay channels. As the non-supersymmetric S-folds are also perturbatively stable, they have been suggested as a potential challenge to the Non SUSY AdS conjecture. However, more evidence of non-perturbative stability is likely needed to make a solid case for non-supersymmetric AdS vacua in quantum gravity.
Keywords: quantum gravity, the swampland, supergravity, type IIB string theory, S-fold, non-compact gauging